FOREIGN LANGUAGE TEACHING ANXIETY AMONG PRE -SERVICE TEACHERS DURING TEACHING PRACTICUM - Dilek Tüfekçi Can (Informascope, 2018)
Research on anxiety in English as a Foreign Language (EFL) commonly focuses on language learning and its related matrices whereas foreign language teaching anxiety (FLTA) has still remained an area of research to be addressed and explored thoroughly. Accordingly, this study was carried out to fill the gap in the literature since when the literature was reviewed, it was found that the few definitions on FLTA are inadequate in covering many other aspects of the concept itself. Thus, the aim of this study was firstly to define a newly emerging concept named FLTA. Secondly, the study aimed to explore pre-service EFL teachers' anxiety provoking factors while they were practising teaching English to young learners at real classroom settings during teaching practicum. The main aim of this study was to make a novel classification on anxiety provoking factors, namely the sources of FLTA. The study was carried out with 25 pre-service EFL teachers studying in the ELT department at Balikesir University. A background questionnaire, interviews, reflections and essay papers were used to collect qualitative data. The results indicated that the pre-service EFL teachers experienced anxiety in teaching English to young learners at real classroom settings particularly related to cognitive, affective and socio-cultural factors.